2023
DOI: 10.1267/ahc.22-00059
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Silymarin on Liver in Experimental in the Sepsis Model of Rats

Abstract: This study, it was investigated whether silymarin has a protective effect by performing histological, immunohistochemical, and biochemical evaluations on the liver damage induced by cecal ligation perforation (CLP). CLP model was established and silymarin was treated at a dose of 50 mg/kg, 100 mg/kg, and 200 mg/kg, by oral one hour before the CLP. As an effect of the histological evaluations of the liver tissues, venous congestion, inflammation, and necrosis in the hepatocytes were observed in the CLP group. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…and reduce MDA levels. [59,60] Similarly, it was observed that the application of SIL (200 mg/kg, po) in a diclofenac-induced lesion model increased the levels of GSH, SOD, and CAT and reduced TNF. [61,62] In agreement, the use of NAC in other injury models is also promising, as shown by the results of treating rats exposed to radiation and treated with NAC (150 mg/kg, i.p.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…and reduce MDA levels. [59,60] Similarly, it was observed that the application of SIL (200 mg/kg, po) in a diclofenac-induced lesion model increased the levels of GSH, SOD, and CAT and reduced TNF. [61,62] In agreement, the use of NAC in other injury models is also promising, as shown by the results of treating rats exposed to radiation and treated with NAC (150 mg/kg, i.p.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to our study, where ethanol and LPS were used as a two‐hit injury model, the results found using thioacetamide‐induced liver cirrhosis showed that SIL administration (200 mg/kg, po) was able to restore antioxidant parameters such as GSH, SOD, and CAT and reduce MDA levels. [ 59,60 ] Similarly, it was observed that the application of SIL (200 mg/kg, po) in a diclofenac‐induced lesion model increased the levels of GSH, SOD, and CAT and reduced TNF. [ 61,62 ] In agreement, the use of NAC in other injury models is also promising, as shown by the results of treating rats exposed to radiation and treated with NAC (150 mg/kg, i.p.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations